Effect of spermine on proliferation of hyphae of Glomus fistulosum, an arbuscular mycorrhizal fungus, in maize roots - Hrselová, H; Gryndler, M (Folia microbiologica, 2000)
Effects of two oligoamines, putrescine and spermine, on proliferation of intraradical hyphae in surface disinfected root segments were studied under axenic conditions in vitro. No significant effects of putrescine were observed. Spermine significantly stimulated hyphal growth at a concentration of about 1.5 mumol/L. High concentration (> 150 mumol/L) caused a strong inhibition of hyphal growth and of the percentage of root segments bearing proliferating hyphae. DL-alpha-difluoromethylornithine, a metabolic inhibitor of polyamine synthesis, caused a significant inhibition of proliferation of the hyphae only in the presence of 2 mumol/L spermine.
Keywords: Zea mays; In Vitro Techniques; eflornithin; Dose-Response Relationship, Drug; Spermine; analýza rozptylu; houby; vztah mezi dávkou a účinkem léčiva; spermin; techniky in vitro; kukuřice setá; Analysis of Variance; Plant Roots; kořeny rostlin; Fungi; Eflornithine